Rebecca of Sunnybrook Farm - Wiggin, Kate Douglas Smith 1856-1923 (Great illustrated classics, 1995)
Talkative, ten-year-old Rebecca goes to live with her spinster aunts, one harsh and demanding, the other soft and sentimental, with whom she spends seven difficult but rewarding years growing up.